(untitled) (TAMADDUN NURI JURNALI, 2025)
The article examines the significance of youth policy at the state level in the Republic of Uzbekistan, the content of the Law «On State Youth Policy», and youth issues in the 2022-2026 Development Strategy of the Republic of Uzbekistan and the «Uzbekistan-2030» Strategy.